1983
DOI: 10.1111/j.1536-7150.1983.tb01708.x
|View full text |Cite
|
Sign up to set email alerts
|

Was Vilfredo Pareto Really a ‘Precursor’ of Fascism.?

Abstract: Abstract. Vilfredo Pareto has been labelled a fascist and ‘a precursor of fascism’ largely because he welcomed the advent of fascism in Italy and was honored by the new regime. Some have seen in his sociological works the foundations of fascism. This is not correct. Even fascist writers did not find much merit in these works, and definitely condemned his economic theories. A s a political thinker he remained a radical libertarian till the end, and continued to express serious reservations about fascism, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

1985
1985
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…Vilfredo Pareto (1922), dismayed at the "astonishing popularity of Marxism in Italy" and "progressive taxation to the disadvantage of the well-off … an arrangement in which taxes are voted by those who do not pay them," saw Fascism "as a spontaneous and somewhat anarchical reaction of a part of the population to the 'Red tyranny,' which the government permitted to run rampant, leaving it to private individuals to defend themselves alone" (p. 148). Pareto died in 1924, shortly after Mussolini appointed him a senator, so his likely reaction to the full reality of Fascism remains debatable (Raico 1996;Cirillo 2006 Raico (1996) argues persuasively that Pareto feared that democracy, unbalanced by emotional electorates and plutocratic special interests, would undo economic liberalism, and thought sacrificing political liberalism the lesser evil. Raico's quotation from Edoardo Giretti, a leading interwar Italian liberal economist, well summarizes such thinking: "If Mussolini with his political dictatorship will give us a regime of greater economic freedom than that which we have had from the dominant parliamentary mafias in the last one hundred years, the sum of good which the country could derive from his government would surpass by far that of evil".…”
Section: Mussolini's Corporatist Epiphanymentioning
confidence: 97%
“…Vilfredo Pareto (1922), dismayed at the "astonishing popularity of Marxism in Italy" and "progressive taxation to the disadvantage of the well-off … an arrangement in which taxes are voted by those who do not pay them," saw Fascism "as a spontaneous and somewhat anarchical reaction of a part of the population to the 'Red tyranny,' which the government permitted to run rampant, leaving it to private individuals to defend themselves alone" (p. 148). Pareto died in 1924, shortly after Mussolini appointed him a senator, so his likely reaction to the full reality of Fascism remains debatable (Raico 1996;Cirillo 2006 Raico (1996) argues persuasively that Pareto feared that democracy, unbalanced by emotional electorates and plutocratic special interests, would undo economic liberalism, and thought sacrificing political liberalism the lesser evil. Raico's quotation from Edoardo Giretti, a leading interwar Italian liberal economist, well summarizes such thinking: "If Mussolini with his political dictatorship will give us a regime of greater economic freedom than that which we have had from the dominant parliamentary mafias in the last one hundred years, the sum of good which the country could derive from his government would surpass by far that of evil".…”
Section: Mussolini's Corporatist Epiphanymentioning
confidence: 97%
“…Mosca, a member of the Italian Senate, took to the floor on different occasions to argue against law bills endorsed by the fascist leader Benito Mussolini. Pareto, an engineer who turned to economics later in life, welcomed the advent of fascism, although fascist ideologists did not find much merit in his works (Cirillo, 1983). The sociologist Michels converted from a revolutionary socialist to a fascist ideologue and accepted a chair of politics from Mussolini's government.…”
Section: Michels: Political Leaders and The 'Iron Law Of Oligarchy'mentioning
confidence: 98%
“…It is common knowledge that the 80−20 rule originated in Pareto in 1896, the principle has found that in most countries about 80% of wealth is controlled by a consistent minority which is about 20% of the population (Franz, 1936). The 80−20 rule has been wildly applied and extended in the fields of sociology, economics, management, quality control, etc (Renato, 1983;Morais & Almeida, 2012). The 80−20 rule focuses on the most important positions of the rankings associated with the number of observations.…”
Section: Proposed Modelmentioning
confidence: 99%